Kebijakan Vaksinasi Covid-19 dalam Perspektif Peraturan Presiden Nomor 14 Tahun 2021 tentang Pengadaan Vaksin - Ali Jumroh Harahap (Inovasi Pratama Internasional. Ltd, 2022)
This study discusses how the regulation of the implementation of vaccination against citizens is the factor that causes community rejection of the implementation of the vaccination program, as well as whether the obligation to carry out vaccinations against citizens is contrary to the human rights and constitutional rights of citizens. The type of this research is normative juridical. The data analysis was carried out in a qualitative descriptive manner. The results showed that the regulation of the implementation of vaccination against citizens is regulated in the Indonesian constitution which guarantees health insurance for its citizens, as embodied in Article 28H paragraph (1) of the Constitution NRI 1945. The factor that causes public rejection of the vaccination program organized by the government is that health workers who have survived Covid-19 still have doubts about being vaccinated, the environment, namely if the people closest to them are against and continue to influence them, there is a possibility that they will also be against the effectiveness of the vaccine. , mindset, values ​​held and people doubt the halalness of vaccines. The obligation to carry out vaccination of citizens is a basic right that must be guaranteed, because health is part of the primary needs of every human being and in the perspective of fulfilling the basic rights of citizens to health, the government is bound by the responsibility to ensure adequate access for every citizen to health services that appropriate and optimal as an effort to respect.